The tangled field : Barbara McClintock's search for the patterns of genetic control - Comfort, Nathaniel C. (Harvard University Press, 2003)
This biographical study illuminates the important yet misunderstood figure of Barbara McClintock, the Nobel Prize winning geneticist. Comfort replaces the myth with a new story, rich with new understandings of women in science.